IMPLIKASI KEGIATAN EKSTRAKURIKULER TERHADAP PENDIDIKAN KARAKTER ISLAM SISWA - Sutriani Sutriani; Nur Hidayat (Raudhah - Proud To Be Professional, 2023)
Abstract This study aims to determine the implications of Islamic character education through extracurriculars in MTs Alkhairaat Sakita. The method used is qualitative through observations in the school. The result of the research is that there are implications of extracurricular activities on the character education of students in MTs Alkhairaat Sakita. Extracurricular activities at the school consist of Pengajian or Yasinan, Hadrah, Pencak Silat, and Scouting. This activity has a positive impact physically and spiritually. Students can practice Islamic teachings, implement Islamic educational values into everyday life, form the personality character of students who are human kamil. Keywords: extracurricular activities, Islamic character education.